Comparison by electron microscopy of intracellular events and survival of Burkholderia pseudomallei in monocytes from normal subjects and patients with melioidosis - Puthucheary, S. D.; Nathan, S. A. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2006)
INTRODUCTION: Burkholderia pseudomallei (B. pseudomallei) has been shown to persist intracellularly in patients with melioidosis, until reactivated by decreasing immunocompetence. We have previously demonstrated by transmission electron microscopy, the internalisation of B. pseudomallei by human macrophages and the occurrence of phagosome-lysosome fusion.